Penerapan Metode Brainstorming dalam Pembelajaran Teks Pawarta Siswa Kelas X.4 SMAN 1 Kedungwuni - Fitriani Putri, Fiky Syahrozad; Alfiah, Alfiah; Sulanjari, Bambang (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2023)
This study aims to describe the results of the application of the Brainstorming method in learning to write news texts for class X.1 students of SMAN 1 Kedungwuni. This is influenced by the lack of student interest in learning Javanese, especially in the material for writing news or news texts. These factors can also cause students to have difficulty understanding the material and lack understanding of vocabulary and language in Javanese subjects. The design used in this study was a pre-experimental design in the form of a one-shot case study involving only one group as a sample without a control group using a purposive sample sampling technique. The data obtained from this study are data collected through a posttest and a questionnaire (questionnaire).After conducting the research, the following results were obtained: 1) in the knowledge aspect competency test, a percentage of 92% was obtained or a total of 32 students received a complete score above the KKM, and there were only 2 students who had not yet reached the KKM. From these acquisitions, the final average value was 89 on the knowledge aspect. 2) in the skills aspect competence test, a percentage of 89% or 31 students whose grades have exceeded the KKM is obtained and 11% or 4 students whose scores have not reached the KKM. From this acquisition, a final average value of 79 was obtained in the skill aspect. Based on the analysis of the data obtained, learning to write an announcement text using the brainstorming method can have an influence on the learning activities of writing an essay text for class X.1 sman 1 Kedungwuni.